Saving culture and ‘microfinance’ practices among beggars in Ibadan, South-West Nigeria (2013)
Begging is a cross-cultural phenomenon that is old, pervasive and complex. The practice is considered a social problem in many societies and had received great attention from scholars, particularly those who believe that understanding its full ramification was central to eradicating it. This study examined an aspect of begging that had mostly been left to speculation: the savings and money-lending practices of beggars. A descriptive qualitative research design was adopted for the study and primary data were generated through 21 In-depth and 5 Key Informant Interviews and Non-participant Observation. The study population was drawn from two purposively seized areas in Ibadan North Local Government Area, Bodija and Sabo, where large concentrations of beggars exist. Participants included beggars, money-handlers, shop y owners and traders. Data were interpreted through content analysis, and sometimes reported through direct quotation. Findings showed that most beggars engage in one form of savings or another, including rotational and fixed-term savings - though some employed the services of retail shop owners to act as bankers. Proceeds of begging constitute an important source of credit acquisition for some traders who took advantage of ease of access and flexible conditionalities to benefit from loans that beggars offerred. Conflicts sometimes arise at the point of reclamation of savings and loan repayment but normative bonds, feelings of mutual-dependency, and general internal control mechanism enabled amicable resolutions. The study concluded that the savings and the “micro-finance” practices of beggars provide new grounds for affirming the utility of this group and recommended that integrative policies should be formulated to sustain the saving culture of beggars.